2020
DOI: 10.3168/jds.2019-17785
|View full text |Cite
|
Sign up to set email alerts
|

Effect of automatic cluster flushing on the concentration of Staphylococcus aureus in teat cup liners

Abstract: Automatic flushing of milking clusters between milking events is a control measure aimed at reducing transmission of mastitis pathogens from infectious milk to a subsequently milked cow. We evaluated the effect of flushing with cold water and flushing with water containing peracetic acid (PAA) on the concentration of Staphylococcus aureus in teat cup liners. Thirty-two clusters in a swing-over milking parlor (Dairymaster, Causeway, Ireland) were subjected to a simulated milking with S. aureus-contaminated milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…Another possible explanation for the association with the milking system may be differences in the cleaning of the teat cup liners, and hence the possibility for bacterial transfer during milking. The flushing or steaming of the teat cup liners between each cow in AMS herds is rarely practiced in parlor systems in Norway and may reduce the transmission of bacteria at milking in AMS herds (Skarbye et al, 2020). Finally, herds with rubber mats as cubicle bases had a higher risk of being case herds compared with herds with mattresses.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for the association with the milking system may be differences in the cleaning of the teat cup liners, and hence the possibility for bacterial transfer during milking. The flushing or steaming of the teat cup liners between each cow in AMS herds is rarely practiced in parlor systems in Norway and may reduce the transmission of bacteria at milking in AMS herds (Skarbye et al, 2020). Finally, herds with rubber mats as cubicle bases had a higher risk of being case herds compared with herds with mattresses.…”
Section: Discussionmentioning
confidence: 99%
“…This is potentially useful information in that farmers can be made aware of the risk of teats becoming chapped in such situations and thereby increasing the risk of developing a case of ITN. In fact, a recent study found that using a flushing system with water alone, without the addition of peracetic acid, was effective in reducing bacterial numbers on the teat skin and may be a way to decrease the risk of ITN ( 47 ). Other potential interventions a farmer could take to reduce the incidence of chapped teats would be to use a post milking teat dip with a high emollient and perform a dynamic milking machine test, especially in the proposed high risk group of first lactation heifers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven [24] that the circulation washing of milk conducting systems with a significant number of parts and assemblies made of aluminum should last from 10 to 20 minutes. At the same time, manufacturers (GEA Farm Technologies, Lely) of milking and dairy equipment recommend processing time in the range of 5-30 minutes [25].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%